Zoom fatigue in review: A meta-analytical examination of videoconferencing fatigue's antecedents - David Beyea; Chaeyun Lim; Alex Lover; Maxwell Foxman; Rabindra Ratan; Alex Leith (Computers in Human Behavior Reports)
As videoconferencing increasingly integrates with modern life, becoming a regular part of work, education, and socialization, the adverse outcomes of increased usage have become a concern to researchers. Multiple scholars have examined Videoconference Fatigue (VF) to identify the causes of this new phenomenon. However, research has revealed conflicting findings regarding the causes of VF, highlighting the need for a meta-analysis. The present study uses quantitative meta-analysis techniques to examine 56 VF antecedents across 38 quantitative studies to examine the extent antecedent variables may affect VF. We collected quantitative studies on VF from Google Scholar, Web of Science, and PsychINFO. The present study organizes and examines the antecedents using two conceptualizations of VF (Bailenson, 2021; Li & Yee, 2022) and the Zoom Exhaustion and Fatigue (ZEF) scale (Fauv ille et al., 2021). We observed the largest effects on VF within the psychological factors category (r = 0.24, k = 28), with “feeling trapped” (r = 0.33, k = 5) being the largest predictor among uncategorized variables. The results for this study provide a map forward for research concerning negative facets of videoconferencing.